Determinants of Tourists’ Willingness to Pay for Tenun Ikat NTT: Uniqueness, Credibility, and Authenticity - Fety Fazriati Rakhman; Nanang Suryadi; Radityo Putro Handrito (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study examines the effects of perceived uniqueness and perceived credibility of geographical indication label on tourists’ willingness to pay for tenun ikat NTT, with perceived authenticity as a mediating variable. The study grounded in Signaling Theory to explain the mechanism of consumer behavior in the purcahase decision-making process for cultural product. Design/methodology/approach – A quantitative explanatory design was employed using a cross-sectional survey of 235 tourists’ seleceted through purposive sampling. Data were analyze using Partial Least Square-Structural Equatoin Modeling (PLS-SEM) using SmartPLS 4.0 software to test both direct and indirect relationships among the construcs. Finding/Results – The results indicates that perceived credibility of GI label has a direct significant positive effect on willingness to pay and perceived authenticity. Perceived uniqueness and perceived credibility of GI label has a direct significant positive effect on perceived authenticity. Perceived uniqueness and perceived authenticity does not directly affect willingness to pay, and mediation analysis shows that perceived authenticity does not mediate the relationships between perceived uniqueness, perceived credibility of GI label, and willingness to pay. The findings indicate that GI label credibility is the only significant direct predictor of willingness to pay, suggesting that institutional trust signals may be more influential than symbolic cultural attributes in shaping tourists' valuation of cultural heritage products. Originality/Value – This study is also conducted to fill the research gap, where studies examining the role of geographical indication labels are still very limited, especially in the cultural craft industry in Indonesia. This study contributes to signaling theory by demonstrating that consumer perceived authenticity as consumers' perception of purchasing behaviour is developed through trust in the GI label's credibility.